Innovative entrepreneurship in Kazakhstan (Journal of Economic Research & Business Administration, 2016)
Innovative entrepreneurship as a special kind of economic activity is the main driving force of the innovation process. Activities of innovative enterprise is profiting from the use of technology and product innovation. In developed countries, about 70% of companies carry out innovations associated with the expansion of the product range in order to develop new market segments. This R & D costs account for about 30% of the investment. One of the main features of innovative entrepreneurship is osuschestvlenie binder (mediating) role between the scientific, technical and industrial spheres. The functioning of innovative business can reduce costs, which have to bear the scientific and technical organizations and business entities associated with the creation of an innovative product or making new scientific and technological solutions to their possible commercial use. The article deals with the formation and development of innovative entrepreneurship in the Republic of Kazakhstan. In particular form of innovative business and do a statistical analysis of innovative business activities.
Keywords: innovative enterprise; business; market; NT.